Polypropylene/glass fiber/nanoclay hybrid composites: morphological, thermal, dynamic mechanical and impact behaviors - Rahman, N.A.; Hassan, A.; Yahya, R.; Lafia-Araga, R.A.; Hornsby, P.R. (2012)
Polypropylene/E-glass fiber/nanoclay were compounded with a twin-screw extruder and injection molded. Thermal, dynamic mechanical, and impact tests were carried out. Differential scanning calorimetry investigations showed that the incorporation of nanoclay into polypropylene/glass fiber composite shifted the melting temperature (T m) to higher values. The degree of crystallinity (X c) was strongly influenced by the presence of the glass fiber and nanoclay in the matrix. Dynamic mechanical analysis showed an increase in storage modulus (Eâ²); indicating higher stiffness of the hybrid composites when compared to the glass fiber composites and the virgin matrix. From the tan Î´ curves, a strong influence of glass fiber and nanoclay content on the magnitude of tan Î´ max value was observed. Impact test showed a reduction in the critical strain energy release rate, G c for hybrid composites with higher nanoclay loading. The stress intensity factor, K c values showed insignificant effect with the presence of nanoclay and GF.